Organic ligand dependent of cobalt-metal-organic framework fabricated electrodes for electrochemical sensing of Rutin - Sivam, Thushatharcchini (2021)
Rutin (RT) (vitamin P) is an electro-active flavanoid mainly found in plants. It is commonly utilize as drug and consumed as a supplement due to its physiological properties. However, consuming Rutin in excessive amount beyond the dose limit may cause health issues in human body. Hence in this research, a facile synthesis of Co-MOF was proposed by using 1,4- benzenedicarboxylic acid (BDC) and biphenyl-4,4-dicarboxylic acid (BPDC), respectively, as ligands (Co-BDC MOF and Co-BPDC MOF) through solvothermal method to effectively detect the presence of RT. The XRD result and FT-IR spectra confirm the formation of Co-BDC MOF and Co-BPDC MOF. Moreover, the SEM images revealed that the Co-BDC MOF possesses a stacked layer of MOF while Co-BPDC MOF shows a needle-like MOF which simply explains that CoDC MOF have larger surface area compare to the other. Further, the Co-BDC and Co-BPDC MOFs were constructed on glassy carbon electrode (GCE) to investigate the detection of RT. The experimental results shows that the organic ligands with different chain length of the synthesized MOF has influenced the interaction with RT. Besides that, Co-BPDC MOF/GCE also exhibited an excellent electrocatalytic activity than the Co-BDC MOF/GCE and bare GCE electrode. To explain this, the high conductivity and excellent interaction with RT are the main reason for Co-BPDC MOF/GCE to exhibit a good electrocatalytic activity. Furthermore, the real sample analysis proves that the Co-BPDC MOF/GCE is capable to determine the existence of RT in pharmaceutical samples with 99.54 to 103.93 % RT recovery. Hence the fabricated sensor in the research exhibited the lowest limit of detection of 0.03 μM (S/N = 3) and the superior sensitivity of 781.43 μA/μM/cm2 with excellent repeatability and reproducibility compare to other published works.